Partisipasi Masyarakat dalam Pelaksanaan Program Keluarga Harapan di Kelurahan Gayamsari Kecamatan Gayamsari Kota Semarang - Nur Aditya Firmansyah; Rosalina Ginting; Supriyono Supriyono (Jurnal Syntax Admiration, 2025)
The Family Hope Program (PKH) is a conditional cash assistance program that aims to alleviate poverty through the family as the initial foundation in achieving family welfare. The Family Hope Program (PKH) is related to the Indonesian Sociology course, which is material on social problems in Indonesia. One of the materials is about poverty. And the Family Hope Program (PKH) is related to the Public Policy course. One of the materials is to alleviate poverty in Indonesia through PKH. However, PKH until now has reduced the poverty rate still resulting in a low number and the independent graduation process of PKH participants is still low, which indicates that this program is only a road in place. This research was conducted using a qualitative method. The selection of research informants was carried out by purposive sampling technique. Data collection, interviews and documentation studies. Data analysis is carried out during data collection then reduces data, presents data, verifies and draws conclusions from research results. The results of the analysis show that community participation in the implementation of PKH in the field is running well and in accordance with applicable regulations. However, there are aspects that need to be improved such as standard operational procedures, the quality of the Government that holds the standard of recipient criteria, there are indications of discretion of the companion that has the potential to deviate.